Elevado Costa e Silva: do artefato ao artifício - Nogueira, André Martins (2017)
This project aims to understand the key issues of contemporary metropolises addressing discontinuities, breaks, fragmentation, flows, real estate depreciation and constitution of the urban landscape, focusing on the Elevado Costa e Silva, in Sao Paulo, Brazil. The work, divided into four main parts, starts with the insertion of “Minhocão” within the context of global transformation of post-industrial urban structures, developing a specific reading of this territory through walking and landscape observation. This project also presents occupation concepts and urban perception, as well as aspects of urban and cultural development of the region, using the definition of specific elements and concepts incorporated for clarification , It uses walking as an intervention action and meaning, by which the landscape (trans) formation will happen, based on the aesthetic and experimental vision. The walking experience and interaction within this reality moves the territory to a surreal atmosphere, making it possible to be read and written – in a rather introspective and personal way – transforming the territory into a narrative sequence. The project then continues to the recognition of the local pre-existence, with its characteristics and life through actions based on otherness. . Finally, after addressing the relevant issues of the selected region and describing the Elevado’s insertion in the urban context in its two levels and territory, it presents considerations about all information collected and recommendations for advancement and continuity in the direction of problems solutions.. The method is developed in a qualitative guidance, with analysis of the concepts proposed in the work of the selected authors